2022
DOI: 10.1002/mp.15800
|View full text |Cite
|
Sign up to set email alerts
|

Spot‐scanning hadron arc (SHArc) therapy: A proof of concept using single‐ and multi‐ion strategies with helium, carbon, oxygen, and neon ions

Abstract: Purpose To present particle arc therapy treatments using single and multi‐ion therapy optimization strategies with helium (4He), carbon (12C), oxygen (16O), and neon (20Ne) ion beams. Methods and materials An optimization procedure and workflow were devised for spot‐scanning hadron arc therapy (SHArc) treatment planning in the PRECISE (PaRticle thErapy using single and Combined Ion optimization StratEgies) treatment planning system (TPS). Physical and biological beam models were developed for helium, carbon, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Qin et al 39 have previously shown that accurate carbon ion dose calculation based on nuclear interaction databases extracted from GEANT are possible. Further work on MonteRay will intend to see how using FLUKA databases performs, especially since de Simoni et al 27 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Qin et al 39 have previously shown that accurate carbon ion dose calculation based on nuclear interaction databases extracted from GEANT are possible. Further work on MonteRay will intend to see how using FLUKA databases performs, especially since de Simoni et al 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Having the capability of simulating helium ions, MonteRay can serve as a fast and accessible tool for ongoing and future research projects, starting with the upcoming clinical trial using helium ions at HIT as well as foreseen helium ion FLASH investigation, helium ion spot‐scanning hadron arc therapy 39,40 or, with a possible extension towards carbon ions in mind, multi‐ion therapy 41,42 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Light ion arcs with single or multi-ions could substantially reduce dose to normal tissue as well as focus high LET into the target. 30,31 However, there are still challenges on the delivery side, which could be remedied by partitioned discrete ion arcs. In a multi-ion setting, the method could potentially be adopted to use different ions in different fractions.…”
Section: Discussionmentioning
confidence: 99%